DIAGNOSIS OF ECHINOCOCCOSIS AND POSTOPERATIVE REHABILITATION LITERATURE REVIEW - Berdiyarova Shokhida Shukurullayevna; Daminov Feruz Asadullayevich; Alamov Temur Sayfiddin ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Echinococcosis is a parasitic disease caused by Echinococcus larvae, which can lead to the formation of cysts in various organs, most often in the liver and lungs. Diagnosis of echinococcosis is a complex process involving clinical assessment, laboratory tests, and imaging techniques. Symptoms can range from an asymptomatic course to severe symptoms due to the pressure of cysts on surrounding tissues. The most common diagnostic methods are ultrasound, computed tomography, and magnetic resonance imaging, which can accurately determine the presence and size of cysts. Serological tests such as ELISA play an important role in confirming the diagnosis.